(untitled) (International Seven Journal of Health Research, 2023)
Introduction: Bariatric, restrictive and mixed (predominantly restrictive or malabsorptive) surgery is a therapy to reduce weight and control associated diseases. This literature review discusses the relevance of procedures approved by the Federal Council of Medicine (CFM) according to bibliographic references of significant scientific evidence. Objectives: To review the techniques currently used in bariatric surgery, advantages and disadvantages. Methods: Literature review of the techniques employed in bariatric surgery, by descriptors in Portuguese (techniques in bariatric surgery, gastric banding, vertical gastrectomy, Roux-en-Y gastric bypasses and biliopancreatic bypass). Results: Gastric banding is a silicone prosthesis wrapped around the stomach, which generates weight regain. Vertical gastroplasty reduces the stomach by a ring-mediated suture with good results but high recurrence. The intragastric balloon is the introduction of a silicone prosthesis with methylene blue, which must be removed after 6 months. Gastric bypass has low mortality and high efficacy, being the most used in Brazil. Vertical gastrectomy preserves the small intestine and partially the stomach, and its low postoperative mortality determines its frequent indication. The Scopinaro technique is 5% of the procedures performed in Brazil, the duodenal switch or vertical gastrectomy with intestinal detour generates nutritional deficiency. Conclusion: Comparing the surgical methods, it is up to the surgeon and the team, the particular analysis to decide which fits best for the patient. However, regardless of the technique used, scientifically it is the conduct with more positive results in the long term, compared to clinical approaches.